Penerapan Kualitas Pelayanan untuk Peningkatan Kepuasan Pasien di Puskesmas Sumberjambe Jember - Yeti Puji Lestari; Nike Norma Epriliyana; Hanif Hadinata Utama (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the implementation of healthcare service quality in improving patient satisfaction at the Sumberjambe Community Health Center in Jember Regency based on the SERVQUAL dimensions. The research method used was descriptive research with a qualitative approach. Data collection was conducted through observation, in-depth interviews, documentation, and distribution of Likert-scale questionnaires to 29 informants, consisting of 25 patients and 4 healthcare workers, using a purposive sampling technique. Data analysis was conducted using the Miles and Huberman interactive model through the stages of data reduction, data presentation, and conclusion drawing, referring to five dimensions of service quality: tangible, reliability, responsiveness, assurance, and empathy. The results showed that, in general, the quality of service at the Sumberjambe Community Health Center was satisfactory, with responsiveness, assurance, and empathy being the main strengths that significantly contributed to patient satisfaction. However, several shortcomings were found in the tangible dimension, particularly related to the cleanliness of the facilities, the comfort of the waiting room, and the availability of adequate parking. The conclusion of this study indicates that good non-physical service quality can significantly increase patient satisfaction. However, this needs to be balanced with improvements in physical facilities to ensure sustainable improvement in the quality of healthcare services at the Sumberjambe Community Health Center. Keywords: Service Quality, Patient Satisfaction, SERVQUAL, Community Health Center, Healthcare